DIAGNOSIS AND TREATMENT DROG INDUCED GINGIVAL HYPERPLASIA - Anyelle Pessoa Dias Dantas, Manoelly; de Oliveira Dantas Filho, Manoel; Freitas Dantas, Rodolfo (Health and Society, 2021)
Gingival hyperplasia is an increase in the number of cells and represents exuberant response of the gingival tissue against local and systemic conditions. Some drugs produce changes in oral tissues. Of calcium channel blockers, nifedipine produce gingival enlargement more often. The objective of this study was to report the case of male patient, 57 years old, who attended the dental clinic Unipê complaining of gingival bleeding and no history of diagnosis after visiting a dentist in other institutions. The patient reported having had chronic kidney disease, hypertension, while making use of drugs: furosemide®, ranitina ®, cyclosporine® and captopril®. On examination, there was an increase of the gingival tissue of uneven surface with lobulations involving the middle third of the lower incisors, tooth mobility and bone loss. Once the diagnosis of gingival hyperplasia drug should clarify the patient and the etiology of the disease and treatment options, such as gingiva plasty, warning of the imminent possibility of relapse. As well as guide the patient to seek medical advice for conducting review of medications. It is relevant to the recognition of a systemic change places, and seek through an interview and performed and directed, to observe the cause-effect relationship.